Speech Perception in Quiet and Noise With an Off the Ear CI Processor Enabling Adaptive Microphone Directionality. Issue 4 (April 2018) - Wesarg, Thomas; Voss, Bettina; Hassepass, Frederike; Beck, Rainer; Aschendorff, Antje; Laszig, Roland; Arndt, Susan
Abstract : Objective: To investigate the impact of the wearing position of an off-the-ear-processor (OTE) on speech perception in quiet and noise. Patients: The study group consisted of 16 adult subjects with bilateral severe-to-profound sensorineural hearing loss, 2 of them unilaterally, and 14 bilaterally provided with cochlear implants. Main Outcome Measures: Speech perception in quiet and noise was measured for frontal presentation with the recipients behind-the-ear processor CP810 or CP910 and the OTE processor Kanso (Cochlear Limited, Sydney, Australia). Additionally, speech performance in noise with the OTE for spatially separated signal and noise sources was assessed. Results: The recipients showed monosyllabic word recognition scores in quiet between 65 and 95% and speech reception thresholds in noise between 2.4 and −5.5 dB SNR with the OTE. For frontal presentation of speech and noise, application of the adaptive directional microphone (Beam) yielded a slight median decrement of 0.6 dB for the speech reception threshold compared with standard directionality. However, huge median improvements, ranging from −3.7 to −11.6 dB, for the three tested conditions with spatially separated sources (S0 NIL, S0 NCL, S0 N180 ) were observed. Conclusion: The beamforming algorithm in the investigated OTE processor provides similar benefits as described in previous studies for behind-the-ear processors in conditions with spatially separated speech and noise sources. Adaptive microphone directionality can be successfully implemented in an OTE processor. The OTE processor's potential to increase usability, comfort, and cosmetics might not be compromised by a deterioration of speech performance.